Germline mutations and genotype–phenotype correlations in patients with apparently sporadic pheochromocytoma/paraganglioma in Korea. (15th November 2013) - Kim, J.H.; Seong, M.‐W.; Lee, K.E.; Choi, H.J.; Ku, E.J.; Bae, J.H.; Park, S.S.; Choi, S.H.; Kim, S.W.; Shin, CS; Kim, S.Y.
<x xml:space="preserve">Abstract</x> The aim of our study was to assess the frequency of germline mutations and develop the genetic testing strategy in patients with apparently sporadic pheochromocytoma/paraganglioma (PPGL) in Korea. We included 53 patients diagnosed with non‐syndromic PPGL without a family history of PPGLs in three referral centers from 2004 to 2011. Succinate dehydrogenase complex B (SDHB), SDHD, Von Hippel–Lindau (VHL), and rearranged during transfection (RET) genes were examined by direct sequencing and multiple ligation‐dependent probe amplification. The study patients were composed of 26 men and 27 women, and mean age was 50.1 ± 13.5 years. The frequency of germline mutations was 13.2% (7/53): RET (n = 2), VHL (n = 1), SDHB (n = 2), and SDHD (n = 2). Six of seven mutation carriers were diagnosed before the age of 50. One of two patients harboring an SDHB mutation had malignant PPGLs. One patient with multifocal head and neck paraganglioma (PGL) and pheochromocytoma (PHEO) carried a SDHD mutation. The carriers of germline mutations in patients with apparently sporadic PPGL were 13.2% in our study. We recommend genetic testing in patients below 50 years and SDHD genetic testing in patients with multifocal PPGLs. In malignant PPGLs, SDHB genetic testing may be performed.